Reflexiones e interrogantes a partir del estudio psicológico de un grupo de condenados a muerte - Ráez de Ramírez, Matilde (1983)
An exhaustive psychological evaluation was done to a group of people condemned to the death penalty. The evaluation included psychological tests, anamnesis and behavioral observation. The results indicate: intelligence within normal range, agresivity, dependence, egocentrism, absence of affectivity, etc. Regarding the defence and relation styles: absence of goals and limits, aloofness, proyection and negation. In terms of personal history the subjects share: absence of the father figure, maternal agresivity and extreme physical punsihment. The authors conclude with some ideas about the meaning of the death penalty.